Tsc2 is not a critical target of Akt during normal Drosophila development. - Dong, J.; Pan, D. (Genes & Development, 2004)
Signaling by insulin and target of rapamycin are both required for cell growth, but their interrelationships remain poorly defined. It was reported that Akt, an essential component of the insulin pathway, stimulates growth by phosphorylating and inhibiting tuberous sclerosis complex 2 (TSC2). Here we evaluate this model genetically in Drosophila by engineering Tsc2 mutants in which the Akt phosphorylation sites are changed to nonphosphorylatable or phospho-mimicking residues. Strikingly, such mutants completely rescue the lethality and cell growth defects of Tsc2-null mutants. Taken together, our data suggest that Tsc2 is not a critical substrate of Akt in normal Drosophila development.